2019
DOI: 10.6018/rcsar.382251
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of the role of Big Data Analytics in reducing the influence of cognitive errors on the audit judgement

Abstract: This systematic literature review provides the association between memory processes, auditors judgement and decision-making process under the influence of cognitive errors. Due to limited cognitive resources, auditors are unable to analyze the population of accounting transactions, therefore, they use sampling and heuristics for information processing. In the context of Big Data (BD), auditors may face a similar problem of information overload and exhibit cognitive errors, resulting in the selection and analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 115 publications
(83 reference statements)
0
9
0
5
Order By: Relevance
“…In particular, Brown-Liburd et al (2015) mentioned that auditors could use data analytics to extract information from many data to help them focus on high-risk audit areas. In addition, Ahmad (2019), Hamdam et al (2021) and Holt and Loraas (2021) found that data analytics could reduce cognitive errors and biased judgments and help auditors to gain a deeper understanding of transactions in the company.…”
Section: Big Data Analytics and Auditor Judgmentmentioning
confidence: 99%
“…In particular, Brown-Liburd et al (2015) mentioned that auditors could use data analytics to extract information from many data to help them focus on high-risk audit areas. In addition, Ahmad (2019), Hamdam et al (2021) and Holt and Loraas (2021) found that data analytics could reduce cognitive errors and biased judgments and help auditors to gain a deeper understanding of transactions in the company.…”
Section: Big Data Analytics and Auditor Judgmentmentioning
confidence: 99%
“…Emerging technologies have boosted the stakeholders' interests since rapid technological advancement is remodeling the accounting profession's nature (Ahmad, 2019). These transformations foster the necessity to explore this knowledge field and offer a comprehensive perception.…”
Section: Future Research Questionsmentioning
confidence: 99%
“…Cumplimiento y pruebas sustantivas: esta es la fase en la que más autores coinciden en que se ve más beneficiada por el uso de tecnologías digitales (ia, big data, rpa, ml y dl). Ahmad (2019), Al-Htaybat y von Alberti-Alhtaybat (2017), , Arnaboldi et al (2017), Issa et al (2016), Kokina y Davenport (2017), Omoteso (2012), Sun (2019), Sun y Vasarhelyi (2018), Zhang (2019) y Zerbino et al (2018) se basan en que con el uso de estas tecnologías, la procedencia y la calidad de los datos se examinan a medida que se recopilan, eventualmente en tiempo real, por ejemplo en las confirmaciones de las aseveraciones (Huang y Vasarhelyi, 2019). En lugar de correr una prueba periódica sobre una muestra de las transacciones, las tecnologías digitales pueden examinar el 100 % de la población de forma continua (Arnaboldi et al, 2017).…”
Section: Tipos De Metodologías Y Enfoques Utilizados En Las Diferentes Publicaciones Científicas Académicas Base De Este Trabajounclassified